2015 IFIP Networking Conference (IFIP Networking) 2015
DOI: 10.1109/ifipnetworking.2015.7145333
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms for distributed feature extraction in multi-camera visual sensor networks

Abstract: Real-time visual analysis tasks, like tracking and recognition, require swift execution of computationally intensive algorithms. Visual sensor networks can be enabled to perform such tasks by augmenting the sensor network with processing nodes and distributing the computational burden in a way that the cameras contend for the processing nodes while trying to minimize their task completion times. In this paper, we formulate the problem of minimizing the completion time of all camera sensors as an optimization p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Throughout the section, we compare TTP to Greedy proposed in [11]. Greedy differs from TTP in that each sensor s ∈ D i always revises its assignment from (x i s , d i s ) to (x i+1 s , d i+1 s ) = (x s , d s ).…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the section, we compare TTP to Greedy proposed in [11]. Greedy differs from TTP in that each sensor s ∈ D i always revises its assignment from (x i s , d i s ) to (x i+1 s , d i+1 s ) = (x s , d s ).…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Our system model is similar to that in [11]. We consider a visual sensor network (VSN) consisting of a set of sensor nodes S, |S| = S, and a set of processing nodes N , |N | = N .…”
Section: System Modelmentioning
confidence: 99%
“…In [17] we proposed algorithms for distributed feature processing for several visual sensors that share a pool of processing nodes, and showed that algorithms that require little coordination may perform reasonably well.…”
Section: Feature Networkingmentioning
confidence: 99%